Analisis Pengaruh Fleksibilitas Kerja (Hybrid Work) Terhadap Kinerja Karyawan: Peran Mediasi Keseimbangan Kehidupan Kerja (Work-Life Balance) - Hulu, Apriaman (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to examine the impact of a hybrid work model on employee performance in the post-pandemic era. Using a quantitative approach, this study also analyzes how work-life balance acts as a mediating variable. Data were collected through questionnaires from 100 respondents in the creative industry sector. Data analysis used Structural Equation Modeling (SEM-PLS). The results show that work flexibility has a positive effect on performance, and work-life balance significantly mediates this relationship. This study recommends that organizations strengthen flexibility policies to improve long-term productivity.